Photocatalytic Activity of n-Alkylamine and n-Alkoxy Derivatives of Layered Perovskite-like Titanates H2Ln2Ti3O10 (Ln = La, Nd) in the Reaction of Hydrogen Production from an Aqueous Solution of Methanol - Sergei A. Kurnosenko (MDPI AG, 2021)
Two series of hybrid inorganic-organic derivatives, obtained via the modification of protonated Ruddlesden–Popper phases H2Ln2Ti3O10 (Ln = La, Nd) with intercalated n-alkylamines and grafted n-alkoxy groups, have been systematically investigated in relation to photocatalytic hydrogen production from a model of 1 mol % aqueous solution of methanol for the first time. Photocatalytic measurements were performed both for bare samples and for their composites with Pt nanoparticles as a cocatalyst using an advanced scheme, including dark stages, monitoring of the volume concentration of the sample in the reaction suspension during the experiment, shifts of its pH and possible exfoliation of layered compounds into nanolayers. It was found that the incorporation of organic components into the interlayer space of the titanates increases their photocatalytic activity up to 117 times compared with that of the initial compounds. Additional platinization of the hybrid samples’ surface allowed for achieving apparent quantum efficiency of hydrogen evolution of more than 40%. It was established that the photocatalytic activity of the hybrid samples correlates with the hydration degree of their interlayer space, which is considered a separate reaction zone in photocatalysis, and that hydrogen indeed generates from the aqueous methanol solution rather than from organic components of the derivatives.